The degree to which kindergarten teachers apply planning, implementation and evaluation skills to acquire scientific conceptsfor the kindergarten child (Journal of Hama University, 2022)
The current research aimed to reveal the degree oapplication of kindergarten teachers to the skills of planning,implementation and evaluation to provide the kindergarten child with scientific concepts, and the research sample consisted of (40) female teachers who were randomly selected from kindergartens affiliated with the public and private sectors. A set of (3) main skills and (35) sub-skills. The researcher made sure of the validity and reliability of the tool using appropriate scientific methods. The research concluded with the following results:1- The teachers of kindergartens have the skills of acquiring the scientific conceptswith abig degree.2- The skill of planning in advance, then the skill of execution, then the correction.3- There are statistical differences in estimating the specimen according tothe variable of scientific qualifier to the benefit of the higher scientific qualifier.4- There are statistical differences in estimating the specimen according to the variable of experienceyears variable to the benefit of experienced for (5-10) years.5- There are statistical differences in estimating the specimen according to the variable of the subordination of thekindergarten to the private ones.